Multiple Sclerosis Biomarkers – moving towards clinical applications - Clarke, Margareta Anna (2019)
Background: Previously proposed multiple sclerosis (MS) biomarkers, including the central vein sign (CVS), which can help differentiate between MS and non-MS, and brain atrophy, which has been shown to predict disability, hold the promise of better diagnosis and monitoring of MS patients. However, findings from research MRI studies need further validation on conventional hospital MRI, before they can be incorporated into clinical practice.